Perceptions of the Legal System and Recidivism: Investigating the Mediating Role of Perceptions of Chances for Success in Juvenile Offenders: - Abate, Anna (Criminal justice and behavior, 2018)
Using a sample of serious juvenile offenders, the current study examined relations between perceptions of the legal system and recidivism, exploring the roles of perceptions of chances for success as a mediator and race/ethnicity as a moderator. The results indicate that in Black and Hispanic juvenile offenders, but not White, perceptions of chances for success mediates the relation between perceptions of the legal system and recidivism. The current study offers support for the notion that interventions aimed at preventing youth from engaging in illegal behaviors may need to be tailored to target racial/ethnic-specific attitudes and foster beliefs in racial/ethnic minority youth that they are capable of future success.